Panoramic view of the Roynton Dry Yard on Moorpark Avenue in San Jose, California - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panoramic view of trays of fruit at the Roynton Dry Yard on Moorpark Avenue in San Jose, California. The original container for the image states that the fruit being dried at the time the image was taken were prunes.